Use of Topical Nasal Anesthesia During Flexible Endoscopic Evaluation of Swallowing in Dysphagic Patients. (March 2015) - Fife, Tim A.; Butler, Susan G.; Langmore, Susan E.; Lester, Scott; Wright, S. Carter; Kemp, Shannon; Grace-Martin, Karen; Rees Lintzenich, Catherine
Objective: This study aimed to determine the effect of topical lidocaine on Penetration-Aspiration Scale (PAS) scores and patient comfort and tolerance of flexible endoscopic evaluation of swallowing (FEES) examinations in dysphagic patients. Methods: Adults with dysphagia referred for swallowing evaluation were recruited to participate in consecutive nonanesthetized and then anesthetized FEES examinations. Under endoscopic visualization, participants consumed 6 swallows consisting of graduated volumes of milk, pudding, and cracker in each condition and recorded their discomfort and tolerance in the 2 conditions. Penetration-Aspiration Scale scores were assigned in blinded fashion for each swallow. Results: Twenty-five adults participated in the study. Although there was no statistically significant effect of anesthesia on PAS scores ( P = .065), the odds of a higher PAS score were 33% higher during anesthetized swallows. The anesthetized condition yielded significantly less discomfort and pain during the examination, significantly less pain and discomfort during insertion and removal of the endoscope, and significantly greater overall tolerance than the nonanesthetized condition. Conclusion: The use of topical lidocaine during FEES may impair swallowing ability in patients with dysphagia, but this result does not achieve statistical significance. Topical nasal anesthesia significantly reduces subjective pain and discomfort and improves tolerance during FEES.